Alpha-Naphthylisothiocyanate triggering G2/M phase arrest and apoptosis in human brain malignant glioma U87MG cells via mitochondrial pathway - Qiang Zhang; Yu-Ting Wang; Shi-Mei Jing; Jian-Yong Chang; Jin-Peng Wang (Bangladesh Pharmacological Society, 2015)
Cancer protective effect of cruciferous vegetables is partly attributed to organic isothiocyanates (ITC) with an N = C = S functional group. Elucidation of the mechanism by which ITCs impart protection against cancer has been the topic of intense research in the past few decades. In this study, we demonstrate that ANIT significantly decreased proliferation and viability of human brain malignant glioma U87MG cells in a dose-dependent manner. The cell cycle analysis showed that ANIT induced significantly G2/M arrest and sub-G1 phase (apoptotic population) in U87MG cells. CDK1 activity assay and Western blot analysis showed that there observed marked reduction in the CDK1/cyclin B activity and protein levels. Pretreatment with specific inhibitors of caspase-3 (Z-DEVE-FMK) and -9(Z-LEHD-FMK) significantly reduced caspase-3 and -9 activity in U87MG cells. Western blot analysis and colorimetric assays also displayed that ANIT caused a time-dependent increase in cytosolic cytochrome c, pro-caspase-9, Apaf-1, AIF, Endo G and the stimulated caspase-9 and -3 activity.